A Project Reoprt on Design and Development of Centroider for Radars - DEEPTHI A R (2003)
INTERNAL GUIDE: THARA ASHWAT H, MVJCE EXTERNAL GUIDE: ANGELA N, LRDE, BANGALORE
Keywords: Centroider for Radars